Analysis of Risk Management Implementation In The Internal Audit Unit (SPI) Politeknik Pelayaran Surabaya Using ISO 31000 - Masita, Ita (IAIN Kendari, 2022)
Risk management aims to minimize the probability and or consequences of unfavorable events and increase risk awareness in strategic and operational decision-making to achieve organizational goals. The Internal Audit Unit (SPI) Politeknik Pelayaran Surabaya is a supervisory unit formed to assist the implementation of Good University Governance by conducting inspections or audits of all work units in the non-academic field. Risk treatment is required through risk management to implement the management function in risk management at SPI Politeknik Pelayaran Surabaya. The risk management process uses a standard risk management process 31000, consisting of a context setting process, risk identification, risk analysis, risk evaluation, risk management, monitoring and review, and communication and consultation. This study uses a descriptive qualitative method with a case study at the Internal Audit Unit (SPI) Politeknik Pelayaran Surabaya, which describes and analyzes risk management using interview and documentation techniques in data collection. Data were analyzed using an interactive model, including data collection, reduction, presentation, and conclusions or verification. The final result of the risk management analysis of the internal audit unit (SPI) Politeknik Pelayaran Surabaya is a form of handling strategy in implementing internal control.